Effects of conditioning activity mode, rest interval and effort to pause ratio on post-activation performance enhancement in taekwondo: a randomized study - Ouergui, Ibrahim; Delleli, Slaheddine; Messaoudi, Hamdi; Bridge, Craig Alan; Chtourou, Hamdi; Franchini, Emerson; Ardigò, Luca Paolo (Frontiers in Physiology, 2023)
Introduction: The present study assessed the effects of conditioning activities, using different effort-to-pause ratios and rest intervals, on taekwondo physical performance. Methods: Twenty-one athletes (13 males and 8 females) (Mean ± SD; age = 20.4 ± 1.4 years) performed a control (CC) and twelve experimental conditions. Each condition contained a standard warm-up (i.e., CC: running at 9 km/h for 10 min) and conditioning activities comprising plyometrics P) or repeated high-intensity techniques (RT) using 1:6, 1:9 and self-selected rest (SSR) ratios, and two rest intervals (3 and 7 min). Athletes then performed a battery of fitness tests: countermovement jump (CMJ), taekwondo specific agility (TSAT), 10s and multiple frequency speed kick test (FSKT-10s and FSKT-mult, respectively). Results: All of the preloads provided higher performance outputs compared to the control trial (all p < 0.05). For CMJ, 1:6 ratio with 3 min induced lower values with RT compared to P (p = 0.037) and 1:9 ratio using 3 min induced higher values with RT compared to P (p = 0.027). Additionally, 1:6 ratio using 7 min induced higher values with RT compared to P (p = 0.016). For FSKT-10, 3 min using 1:6 induced higher values with P compared to RT, while RT induced higher values with 7 min using 1:6 ratio compared to P (both p < 0.001). Moreover, 3 min using 1:9 ratio induced higher values with P compared to RT (p = 0.034), while RT induced higher values with 1:9 ratio using 7 min compared to P (p < 0.001). Finally, 3 min using SSR ratio induced higher values with RT compared to P (p = 0.034). Conclusion: Plyometrics and RT activities improved performance with plyometrics requiring shorter rest interval to induce potentiation effects compared to RT, which required longer interval.